Wanting - Flanagan, Richard (Atlantic Books, 2010)
1841. In the remote penal colony of Van Diemen's Land, a barefoot aboriginal girl wearing a red silk dress sits for her portrait. She is Mathinna, the adopted daughter of the island's governor, Sir John Franklin, and his wife, Lady Jane, and the subject of a grand experiment in civilization - one that will determine whether science, Christianity and reason can be imposed in place of savagery, impulse and desire. A quarter of a century passes. Somewhere in the Arctic, Sir John Franklin has disappeared, along with his crew and two ships, on an expedition to find the fabled Northwest Passage. England is horrified as reports of cannibalism filter back from search parties, no one more so than the most celebrated novelist of the day, Charles Dickens, for whom Franklin's story becomes a means to plumb the frozen depths of his soul. As several lives become conjoined by unexpected events and tragedies, Wanting transforms into a remarkable meditation on the ways in which desire - and its denial - shape our lives.
9781848870772
Keywords: Franklin; Dickens; Historical fiction; Aboriginal Australians; Interracial adoption